2016
DOI: 10.1111/chd.12429
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, morphology, and progression of bicuspid aortic valve in pediatric and young adult subjects with coexisting congenital heart defects

Abstract: The morphology of BAV, the pattern and progression of aortic dilatation, and the severity of aortic valve disease vary in pediatric and young adult patients with BAV and coexisting CHD. However, there was no significant BAV disease progression when associated with these CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 25 publications
(43 reference statements)
4
37
0
2
Order By: Relevance
“…Progression to aortic stenosis has been associated with advancing age in children with isolated bicuspid aortic valve, similar to our results. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progression to aortic stenosis has been associated with advancing age in children with isolated bicuspid aortic valve, similar to our results. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Patients with isolated bicuspid aortic valve are generally asymptomatic and follow a rather benign course, but one recent investigation found that the severity of aortic regurgitation increased with age. [ 11 ] However, patients with bicuspid aortic valve and coexisting congenital heart diseases, such as an interrupted aortic arch, coarctation of the aorta, or ventricular septal defect may be more susceptible to complications than in the general population. [ 12 13 14 ] Bicuspid aortic valve morphology is a common risk factor for valve-related complications, for example, dilation of the aorta, which may be present at birth and could progress over time irrespective of the functional state of the valve.…”
Section: Introductionmentioning
confidence: 99%
“…CoA often coexists with other left heart obstructive lesions like mitral stenosis, subaortic stenosis and aortic stenosis. About 50-60% patients with coarctation of the aorta or interrupted aortic arch have a BAV [8]. Compared to right-sided lesions, left-sided cardiac obstructions are more frequently seen in males than female [2].…”
Section: Epidemiologymentioning
confidence: 99%
“…A bicuspid aortic valve (BAV) is the most common congenital heart disease with a reported incidence of about 1% to 2% in the general population (1)(2)(3)(4)(5). It may occur as either an isolated cardiac defect or in association with other congenital heart malformations (1,(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…A bicuspid aortic valve (BAV) is the most common congenital heart disease with a reported incidence of about 1% to 2% in the general population (1)(2)(3)(4)(5). It may occur as either an isolated cardiac defect or in association with other congenital heart malformations (1,(3)(4)(5)(6)(7)(8)(9)(10). The most well-known anomaly associated with a BAV is aortopathy (1,(3)(4)(5)(6)(7)(8)(9)(11)(12)(13), which include coarctation of the aorta (CoA), aortic dissection, or aortic aneurysm.…”
Section: Introductionmentioning
confidence: 99%